2016
DOI: 10.1007/978-1-4939-6649-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Pseudomonas syringae pv. tomato Effector Proteins in Plants

Abstract: Summary Animal and plant pathogenic bacteria use type III secretion systems to translocate proteinaceous effectors to subvert innate immunity of their host organisms. Type III secretion/effector system is a crucial pathogenicity factor in many bacterial pathogens of plants and animals. Pseudomonas syringae pv. tomato (Pst) DC3000 injects a total of 36 protein effectors, which target a variety of host proteins. Studies of a subset of Pst DC3000 effectors demonstrated that bacterial effectors, once inside the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Several studies have demonstrated that the effector proteins from pathogenic bacteria are targeted to specific subcellular compartments in cells, where they alter the physiological properties of the cell and suppress innate immunity (Alfano and Collmer, 2004;Kay and Bonas, 2009;Choi et al, 2013;Aung et al, 2017). Thus, the spatiotemporal localization of the effectors is crucial for their function inside the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the effector proteins from pathogenic bacteria are targeted to specific subcellular compartments in cells, where they alter the physiological properties of the cell and suppress innate immunity (Alfano and Collmer, 2004;Kay and Bonas, 2009;Choi et al, 2013;Aung et al, 2017). Thus, the spatiotemporal localization of the effectors is crucial for their function inside the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…T3E protein localization is important for the function of T3Es [ 32 ]. As previously reported, XopN is localized at the plasma membrane (PM) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gold particles were coated with plasmids that express YFP (which can move from transformed cells to adjacent cells through PD in Arabidopsis epidermal cells) and ERtrapped CFP (ER-CFP; which cannot move beyond transformed cells). Plasmid-coated particles were bombarded into leaves of wild-type Col-0, 35S-HopO1-1, and 35S-HopO1-1 DD transgenic plants following the protocol described previously (Thomas et al, 2008;Faulkner et al, 2013;Aung et al, 2017). Fluorescent signals were detected at ;20 h after bombardment using confocal microscopy.…”
Section: Hopo1-1 Alters Pd-mediated Cell-to-cell Molecular Traffickinmentioning
confidence: 99%
“…To examine PD-dependent molecular flux, a microprojectile bombardment approach combined with confocal imaging was adopted as previously described (Thomas et al, 2008;Faulkner et al, 2013;Aung et al, 2017). In short, 20 mg of 1.0-mm gold particles (Bio-Rad) was soaked in 70% (v/v) ethanol for 15 min and rinsed with 1 mL of sterile distilled water three times.…”
Section: Transient Expressionmentioning
confidence: 99%